ECONOMIC DIAGNOSTICS IN THE SYSTEM OF INFORMATION SUPPORT FOR MANAGEMENT DECISION-MAKING - KOZLOVA, Valeria (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article updates the problem of the role, place and informative possibilities of economic diagnostics for making managerial decisions regarding the innovative development of the enterprise. A significant number of scientific publications of Ukrainian and foreign economists devoted to various aspects of managerial innovations were considered, and the need for a systematic search for ways of innovative transformation of managerial decision-making for the effective development of enterprises was revealed. Analytical models of managerial decision-making based on knowledge were analyzed, the necessity of using business analytics for multi-criteria decision-making was revealed. The factors of the impact of analytical information on the quality of management decisions regarding innovative development, technological improvement, productivity growth and value creation in the organizational environment are analyzed. The need to develop a system of information and analytical support for enterprise management using an analysis mechanism, the implementation of which is based on monitoring the achievement of predetermined evaluation criteria, is substantiated. The role of economic diagnostics in increasing the efficiency of management of the enterprise's activities has been clarified. It is proposed to consider economic diagnostics as a leading element of the information support system of the management decision-making process, both to identify the causes of disagreements and to find factors for accelerating innovative transformations. The established diagnostic indicators of the system of innovative development of the enterprise are considered and the author's approach to determining the factors of coordination is proposed. Thus, it was established that the use of economic diagnostics in the management of innovative development allows to increase the informative relevance for making conceptual management decisions.. Further research is proposed to focus on the development of methodological principles for the introduction of economic diagnostics into the system of management decision-making in operational, tactical and strategic directions.
Keywords: innovative transformations; management influence; control mechanism; information relevance; coordination factors; development efficiency